Igbo Speech Surrogacy: Preliminary Findings Based on the Oja Flute - Carter-Ényì, Aaron; Amadi, Nnaemeka C.; Carter-Ényì, Quintina; Chukwudozie, Charles; Nwankwo, Jude; Omodoro, Ebruphiyor (Frontiers in Psychology, 2021)
This research report presents analyses of recordings from the Ìgbò culture of southeastern Nigeria of an ọ̀jà flute player, a female speaker, and a male speaker. After a prepared performance, the participants completed two tasks: (1) mapping speech to flute playing and (2) identifying phrases played on the flute. Contour analysis is applied to annotated recordings to study the mapping of speech tone and rhythm from voice to instrument in parallel utterances by the three participants (male, female, flute). Response time between the flute playing and spoken phrase identification indicates each prompt’s relative clarity. Using a limited, but not predetermined, inventory of related praise epithets, participants were able to successfully convert speech to music and music to speech. In the conversion of speech to music, we found that declination was not part of the mapping, indicating it is a phonetic artifact of speech and does not carry a functional load. In the identification of surrogate phrases played on the flute (music to speech), we found that dialectical variation caused some misidentification, because idioms known in one area of the Igbo dialect cluster are not known throughout the region, although ọ̀jà speech surrogacy is found throughout the region. Possibilities and predictions for further research are presented.